E-learning multimodal system for teaching and learning programming - Teixeira, Ana (2016)
The high failure rates and abandonment are common in introductory programming courses in many higher education institutions worldwide. Different solutions have been proposed in literature trying to solve the problem but the situation remains virtually unchanged. Some members of this group also contributed with computer-based tools and different studies to understand and reduce this problem. Among the works carried out, the importance of investing in motivational aspects and the ability to solve problems is highlighted. This paper describes a new approach in order to contribute in solving this problem. The idea is to investigate the psychophysiological response of individuals during testing. The goal is to measure aspects of interest like the ability of abstraction, emotions, concentration, frustration, immersion, load/stress and cognitive level, in complex scenarios such as the resolution of programming problems. Thus, we intend to use new forms of interaction as Brain Computer Interfaces (BCI), eyetracking and other low-cost instruments (e.g.: BITalino) using body signals to extract information of interest. This information will be included in an e-learning system adapting its interface according to the users actions.